Hear #metoo in India: news, social media, and anti-rape and sexual harassment activism - Guha, Pallavi (Rutgers University Press, 2021)
Introduction and Historical Background -- Framing of Rape in News Media and its Impact on Feminist Activism and Journalists #metooindia Including Themes -- The Heart Doesn't Bleed for Everyone: Selective Outrage and Activism -- The Successes and Failures of Transnational Hashtag Movements -- Moving Forward: Learning from Anti-Rape Feminist Movements.